ISLAMIC RELIGIOUS EDUCATION AND THE GLOBAL ETHICS: OPPORTUNITIES AND CHALLENGES TOWARDS PEACE EDUCATION IN INDONESIA - Evita Apriliana; Mahfud Junaedi; Ikhrom Ikhrom (LP2M Universitas Ibrahimy, 2023)
The world has many problems, economic interests, chaos, and wars. Man needs a binder to prevent man (countries) from being able to do something that only benefits himself and harms others. Thus, global ethics as a minimalist ethic is needed in this world. The goal is that there be peace and order. This article aims to construct an idea of creating peaceful education through Islamic Religious Education with a global ethical perspective. This research confirms that the main points of global ethics are relevant to Islamic religious education in Indonesia regarding Islamic teachings and Government Regulations. The integration of global ethics in Islamic Religious Education can be implemented in Indonesia. On the other hand, there are challenges to integrating global ethics in learning; how can teachers provide students with an understanding of the universal values of global ethics in Indonesia context of a plural society? The leading global ethics precepts must be included in the Islamic religious education curriculum at the basic, secondary, and higher levels. This study is devoted to developing a rudimentary idea of Islamic religious education from a global ethical standpoint. As a result, additional research on Islamic religious education from a global ethical viewpoint is required.